1998
DOI: 10.1515/hfsg.1998.52.6.563
|View full text |Cite
|
Sign up to set email alerts
|

Radial Striation of the S2Layer in Mild Compression. Wood Tracheids ofPinus radiata

Abstract: The fine structure of the tracheid walls in Pinus radiata mild compression wood was examined by field emission scanning electron microscopy (FE-SEM) and transmission electron microscopy (TEM). On transverse-fractured surfaces the S 2 layer of tracheid walls exhibited distinct radial structures when observed with the FE-SEM. The TEM observations of ultrathin sections of samples from similar regions showed the S 2 layer with radial striations, corresponding in their direction to the radial structures seen with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 12 publications
(13 reference statements)
1
14
0
Order By: Relevance
“…3). The presence of radial features in the S 2 -layer in tracheids of normal and mild compression wood of Pinus radiata (Singh et al 1998;Singh & Donaldson 1999) and in normal wood of Norway spruce (Singh & Daniel 2001) has been confirmed by TEM of ultra-thin sections. These researchers have shown nano-level lignin inhomogeneity in sinuous radial profiles across the thickness of the S 2 -layer, and on the basis of this pattern of lignin micro-distribution they have predicted that the microfibrillar bundles are randomly distributed across the S 2 -layer.…”
Section: The S 2 -Layer Lamellationmentioning
confidence: 67%
See 1 more Smart Citation
“…3). The presence of radial features in the S 2 -layer in tracheids of normal and mild compression wood of Pinus radiata (Singh et al 1998;Singh & Donaldson 1999) and in normal wood of Norway spruce (Singh & Daniel 2001) has been confirmed by TEM of ultra-thin sections. These researchers have shown nano-level lignin inhomogeneity in sinuous radial profiles across the thickness of the S 2 -layer, and on the basis of this pattern of lignin micro-distribution they have predicted that the microfibrillar bundles are randomly distributed across the S 2 -layer.…”
Section: The S 2 -Layer Lamellationmentioning
confidence: 67%
“…Some recent studies have reported the S 2 -layer to have some kind of radial lamellation (Sell & Zimmerman 1993;Sell 1994b;Larsen et al 1995;Singh 1997;Schwarze & Engels 1998;Singh et al 1998;Singh & Donaldson 1999;Zimmermann & Sell 2000;Singh & Daniel 2001). The idea of radial lamellation in conifers is not new, and was discussed earlier by Bailey (1938) and also found in compression wood by Wardrop and Dadswell (1950).…”
Section: The S 2 -Layer Lamellationmentioning
confidence: 93%
“…By contrast, Schwarze and Engels (1998 [20] ) found radial structures in normal wood of Norway spruce (Picea abies) after soft rot degradation but no such structure in tension wood of Norway spruce. In an ultrastructural investigation using TEM in addition to FE-SEM, Singh and coworkers (1998 [26] ) found both radial striations of cellulose aggregate agglomerations and of lignin in compression wood of Pinus radiata. These radial structures were in the order of 30 to 300 nm.…”
Section: Discussionmentioning
confidence: 99%
“…For instance transmission electron microscopic investigations [Singh et al 1998;P6hler 1995] and decomposition studies of the cell wall with fungi [Schwarze, Engels 1998] also provide additional confirmation of radial arrangement of lignin and/or cellulose of the $2 layer. For instance transmission electron microscopic investigations [Singh et al 1998;P6hler 1995] and decomposition studies of the cell wall with fungi [Schwarze, Engels 1998] also provide additional confirmation of radial arrangement of lignin and/or cellulose of the $2 layer.…”
Section: Discussionmentioning
confidence: 99%